A Profile Of Demographic And Nutritional Status Of Shompens - The Primitive Mongoloid Tribe Of Great Nicobar - Rao V. G; Sugunan A. P; Sehgal S. C (Wolters Kluwer Medknow Publications, 1998)
Research Question: What is the health and nutritional status of Shompens â€" the primitive mongoloid tribe of Great Nicobar. Objectives: i) To study the health & nutritional status of the Shompens. ii) To identify their common health problems. Study design: Cross-sectional Setting: Bands of Shompens â€" the primitive mongoloid tribe of Great Nicobar. Study variables: Age, sex, marital status, height, weight, mid arm circumference, fat fold thickness, nutritional status, health problems, health problems. Statistical analysis: Proportions